DOI: 10.26686/wgtn.16967395
|View full text |Cite
|
Sign up to set email alerts
|

A Time of Travelling Hopefully: a Mixed Methods Study of Decision Making by Women and Midwives about Maternity Transfers in Rural Aotearoa, New Zealand

Abstract: <p>Making decisions about the reasons for, and the timing of transfer to specialist care from rural maternity care were examined in this study. This is a time when women and midwives 'travel hopefully' through labour and birth aware of their rural context. A Mixed Methods Research (MMR) approach was used to gather data from a national survey of rural maternity units together with individual and small group interviews of women and of midwives. A modified Concurrent Mixed Model Design was used to structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The appreciation of rural women and the commitment to rural communities have been found in other research into rural midwives in New Zealand (Crowther, 2016;Kyle & Aileone, 2013;Patterson 2009). A common thread in the survey was that midwives identified that working autonomously is an essential and central tenet of rural practice and most commented on this positively.…”
Section: Strengths: Rural Midwives' Passion and Skillsmentioning
confidence: 70%
See 4 more Smart Citations
“…The appreciation of rural women and the commitment to rural communities have been found in other research into rural midwives in New Zealand (Crowther, 2016;Kyle & Aileone, 2013;Patterson 2009). A common thread in the survey was that midwives identified that working autonomously is an essential and central tenet of rural practice and most commented on this positively.…”
Section: Strengths: Rural Midwives' Passion and Skillsmentioning
confidence: 70%
“…My biggest challenges are the isolation -the closest midwife lives 85km away, the numbers (it's financially unsustainable to call this a caseload), and time off -there is no time off to be able to do anything reliable with my family. (Kim, Forum) The issues related to the time associated with travel, isolation and maintaining a sustainable workload have been highlighted in other research on rural midwifery in New Zealand (Crowther, 2016;Kyle & Aileone, 2013;Patterson 2009). In addition, many participants wrote about the impact of adverse weather conditions.…”
Section: Vulnerabilities: Travel Isolation and Social Determinants Of...mentioning
confidence: 99%
See 3 more Smart Citations